Propensity towards entrepreneurial education among students of higher learning institutions / Nur Lailatul Husna Mohammad Yusof, Abdul Malek A.Thambi and Nur Hazwani Zolkifly - Nur Lailatul Husna, Mohammad Yusof; Abdul Malek, A.Thambi; Nur Hazwani, Zolkifly (Universiti Teknologi MARA, Perak, 2018)
This study attempts to examine the level of entrepreneurial propensity among students of Higher Learning Institution in the Northern region of Peninsular Malaysia. The objective of this paper is to examine the relationship between the entrepreneurship education and propensity towards entrepreneurship practices. A total of 300 students are taken from two campuses which are UiTM Seri Iskandar Campus and UiTM Tapah Campus. The questionnaires are personally distributed to these respondents. There are four factors that had been tested on the entrepreneurial propensity with the use of appropriate measure using the 5-point Likert scaling. All the constructs and variables are systematically developed and hypotheses. An empirical test carried out on the data gathered from questionnaires demonstrates that four entrepreneurship education variables which are University’s role,university’s curriculum, role model as well as internship programme are found to have statically significant relationship on the propensity towards entrepreneurship. Finally, based on the findings, the discussion of the study has been forwarded.